MAN’S CHOICE PROBLEM IN THE GLOBALIZATION EPOCH - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the philosophical analysis of man’s status and his education in the 21st century while choosing his further way of existence in the complicated globalized world.